A study on the effects of quarterly financial reports on systematic risk and return on assets: A case study of Tehran Stock Exchange - Roozbeh Hedayat Mazhari (Management Science Letters, 2013)
Financial statements are considered as primary sources of information for most investors to make investment decisions. A crystal clear and comprehensive annual report helps many interested parties about the performance of any business unit. However, many rules and regulations ask management teams of organizations to provide quarterly financial results. In this paper, we perform an empirical investigation to study the effects of quarterly financial reports on three ratios including systematic risk, return on assets and firm size. The proposed study gathers the necessary data from 72 firms listed on Tehran Stock Exchange over the period of 2000-2006. The study determined the performances of these 72 firms before and after the releases of three quarterly reports and using Freedman test determined whether there were any meaningful differences between two groups of data or not. The results of Freedman test indicate that there were not any meaningful differences between stock performance and systematic risk before and after quarterly results. The survey also examines the relationship between systematic risk and size of firms using Pearson correlation test and the results indicate there were some meaningful differences size and systematic risk.